Verbal Irony in a TV Series The Office (US) Season 2 - Nabila Nurul Hasyim; Sharifah Hanidar (Lexicon, 2022)
Verbal irony as a figurative language has been conceived in everyday life as its use is common when people communicate with each other. It enables the speaker to express negative intention towards the hearer as well as producing humor elements. This study aims to analyze verbal irony in the sitcom The Office (US)  from Pragmatics perspective, which focuses on the identification of its forms and their manifestations in arousing humor. The data of this study were collected from season 2 of The Office (US) that consists of 22 episodes. They were observed, transcribed, analyzed, and classified into the category proposed by Gibbs (2000). The utterances that contain humor were marked and analyzed by applying the theory proposed by Garmendia (2007). The result shows that from 97 occurrences that were identified, all five types of verbal irony (sarcasm, jocularity, rhetorical question, hyperbole, and understatement) were found, with sarcasm as the most frequently used type. The analysis also revealed that the disparity that emerges from verbal irony leads to humor creation.